The christology of Theodore of Tarsus: the Laterculus Malalianus and the person and work of Christ - Siemens, James (Studia traditionis theologiae, 2010)
Theodore of Tarsus served as archbishop of Canterbury for twenty-two years until his death in 690, aged eighty-eight. Because the only significant record we had of Theodore was that contained in Bede's Historia, until recently it was very difficult to say anything about his life before this appointment, and even more difficult to determine anything about his thought. All of that changed in the last half of the twentieth century, when the discovery of some biblical glosses from Canterbury was revealed and the ensuing scholarship uncovered more of Theodore's work than had previously been known. The Laterculus Malalianus is a text that benefited from treatment in this period. This present work examines the Laterculus for what it has to say about the person and work of Christ, and establishes that Theodore's main theological inspiration was Irenaeus of Lyons and the concept of recapitulation, even while he cast his thought in language heavily drawn from the Syriac East, and Ephremthe Syrian in particular